An Application of Al-Islah Method wa Tagyr in Islamic Education Learning to Achieve Mental Health - Nurti Budiyanti; M Rindu Fajar Islamy; Muhammad Parhan (CV. Creative Tugu Pena, 2025)
This study investigates the implementation of the Al-Islah wa Tagyīr method in Islamic Religious Education (PAI) as a means to promote students’ mental health. The Al-Islah wa Tagyīr method, which emphasizes self-improvement and transformation through spiritual and moral approaches, is employed to enhance students’ psychological well-being. A qualitative approach was adopted using a case study method in universities that have applied this method in PAI learning. Data were collected through observation, in-depth interviews, and document analysis. The findings reveal that the application of the Al-Islah wa Tagyīr method strengthens students’ religious and psychological dimensions, positively influences emotional regulation, enhances self-confidence, and fosters healthier social interactions. Consequently, the method has been shown to be effective in supporting the attainment of improved mental health among students. This research contributes to the enrichment of Islamic Religious Education by integrating mental health perspectives into pedagogical practices. Specifically, it offers a holistic model of PAI learning that not only develops religious knowledge and moral character but also supports psychological resilience and well-being. The study provides theoretical insights into the synergy between spirituality and mental health and offers practical implications for educators, policymakers, and curriculum developers in creating more comprehensive educational strategies that address both cognitive and emotional aspects of student development.